A Review on Degradation Improvement of Sisal Fiber by Alkali and Pozzolana for Cement Composite Materials - Tsion Amsalu Fode; Yusufu Abeid Chande Jande; Thomas Kivevele; Nima Rahbar (Journal of Natural Fibers)
Sisal fiber employment in concrete improves its post-crack strength, but sisal fiber degrades due to moisture and cement mineralization. Many researchers used alkaline and pozzolanic techniques to treat sisal fiber in cement composite materials. However, which treatment method is most effectively used to modify sisal fiber for sustainable use in cementing materials has yet to be well known. Therefore, this review highlights the effect of alkaline and pozzolanic materials on sisal fiber treatment. The review of various studies found employment of 1–1.5% of treated sisal fiber by alkaline or pozzolana reduces workability and improves the mechanical properties, especially as many authors found the treatment of sisal fiber by pozzolanic material averagely improves compressive strength and splitting tensile strength of cementing materials by 21.75% and 36.53%, while alkaline treatment 12.83% and 14.92% respectively, compared to control mixture. Besides these, many studies found the treatment of sisal by either alkaline or pozzolana significantly lessens water absorption capacity, improves the thermal resistivity of the fiber, improves fiber adhesion with the matrix, makes rougher microstructure of fiber surface. However, many studies reported alkaline treatment to have drawbacks in the disposal of alkaline chemicals that increase environmental pollution, at high concentrations cause fiber deterioration, and chemical production cost.